Complaints of Musculoskeletal Disorders in Cleaning Officers at Hospital - Asrain Hasibuan (Pena Cendekia Insani, 2020)
Introduction: A heavy workload can have a negative effect onworkers' health, one of which is the appearance of MusculoskeletalDisorders or complaints of pain, injury, or abnormalities in theskeletal muscles, which include the nerves, tendons, ligaments,muscles, and joints; this can have a negative effect on worker quality.A Nordic Body Map can be used to quantify musculoskeletaldisorders. The purpose of this study was to ascertain the relationshipbetween workload and Musculoskeletal Disorder complaints amongcleaning staff at Kota Pinang Hospital in Labuhanbatu SelatanRegency . Method: This type of research employs a quantitativeapproach with a cross-sectional design. The research subjects were53 cleaners at Sibubuan Hospital in Labuhanbatu Selatan Regencywho were recruited using a total sampling technique or by taking arepresentative sample of the entire cleaner population at Kota PinangHospital in Labuhanbatu Selatan Regency . The chi square test wasused to process and analyze the data, which was done using the SPSSversion 22 computer program. Result : According to the study'sfindings, based on frequency of respondents' workloads at heavyworkloads is 37 (69.8%), light workloads are 16 (30.2%) of the totalsample. Frequency of service period of respondents who worked 1-5years was 40 (75.5%), respondents who worked 6-10 years were 13(24.5%) of the total sample. The frequency of high musculoskeletaldisorders is 37 (69.8%), low musculoskeletal disorders are 16(30.2%) of the total sample. Conlusion The high incidence of MSDSin hospital cleaners, the length of work, workload and age are factorsthat should be suspected of having an impact on the incidence ofMSDS in hospital cleaners.